Interstitial cystitis/bladder pain syndrome and recurrent urinary tract infection and the potential role of the urinary microbiome. Issue 2 (June 2020) - Bhide, Alka; Tailor, Visha; Khullar, Vik
Interstitial cystitis/bladder pain syndrome and recurrent urinary tract infections carry significant burden for those affected. As women enter the menopause, other factors may influence how these conditions manifest. The urinary microbiome has shown that the urine contains extensive numbers of bacteria. There is some evidence to suggest that it is altered depending on the menopausal state of the individual. It is possible that this alteration may go on to influence how the disease course of interstitial cystitis/bladder pain syndrome and recurrent urinary tract infections runs in the post-menopausal group. The review will explore these two conditions and the potential role of the urinary microbiome.